ACCOUNTING, TAXATION AND CONTROL OF BEEKEEPING PRODUCTS PRODUCTION: METHODS, TOOLS AND PROSPECTS - BEZDUSHNA, Yuliia; SHULHA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study is devoted to the analysis of modern approaches to accounting and control in the beekeeping industry, which is an important factor in increasing the efficiency of beekeeping, ensuring product quality and its competitiveness in the market. The paper examines the essence and significance of accounting for beekeeping products, its main indicators and methods of keeping them. Special attention is paid to the peculiarities of taxation in the beekeeping industry during martial law. The role of digital technologies in improving accounting and control of products is studied, in particular the use of automated apiary management systems, the Internet of Things (IoT), blockchain technologies, artificial intelligence and cloud services. The prospects for the application of these technologies to increase the transparency and accuracy of accounting processes, as well as improve the traceability of honey and other bee products, are identified. The prospects for the development of accounting and control of beekeeping production are identified, among which the digitalization of accounting processes, improvement of the regulatory framework, improvement of product quality control, development of international certification and expansion of sales markets are highlighted. The conclusions are that the introduction of modern methods and technologies into accounting and control of beekeeping products will contribute to increasing the efficiency of the industry, minimizing risks, improving product quality and its compliance with international standards, which, in turn, will open up new opportunities for the export of Ukrainian honey and bee products.